Microelectromechanical Systems Based on Magnetic Polymer Films - Denisa Ficai; Marin Gheorghe; Georgiana Dolete; Bogdan Mihailescu; Paul Svasta; Anton Ficai; Gabriel Constantinescu; Ecaterina Andronescu (Micromachines, 2022)
Microelectromechanical systems (MEMS) have been increasingly used worldwide in a wide range of applications, including high tech, energy, medicine or environmental applications. Magnetic polymer composite films have been used extensively in the development of the micropumps and valves, which are critical components of the microelectromechanical systems. Based on the literature survey, several polymers and magnetic micro and nanopowders can be identified and, depending on their nature, ratio, processing route and the design of the device, their performances can be tuned from simple valves and pumps to biomimetic devices, such as, for instance, hearth ventricles. In many such devices, polymer magnetic films are used, the disposal of the magnetic component being either embedded into the polymer or coated on the polymer. One or more actuation zones can be used and the flow rate can be mono-directional or bi-directional depending on the design. In this paper, we review the main advances in the development of these magnetic polymer films and derived MEMS: microvalve, micropump, micromixer, microsensor, drug delivery micro-systems, magnetic labeling and separation microsystems, etc. It is important to mention that these MEMS are continuously improving from the point of view of performances, energy consumption and actuation mechanism and a clear tendency in developing personalized treatment. Due to the improved energy efficiency of special materials, wearable devices are developed and be suitable for medical applications.